Evaluation of the Integrated and Champion Puskesmas Program (PUSPA) 2023 - Vira Marcelina; Maharani; Nadia Hilma Raudlah; Syipa Rahmawati (Jurnal Perencanaan Wilayah dan Kota, 2024)
Integrated and Champion Puskesmas (PUSPA) is one of the programs created to overcome health problems in West Java Province. This study aims to evaluate the achievements of the PUSPA program in 2023, which is included in the 2018-2023 West Java Province Regional Medium-Term Development Plan (RPJMD) document, to ensure the implementation of the PUSPA program has successfully achieved the target of each indicator and to find out the factors that affect the achievement of each indicator. This study uses an ex-post evaluation model and employs quantitative descriptive and comparative analysis techniques. The results of the study show that from 3 indicators of the achievement of the non-communicable disease program, only 1 program was achieved, namely the presentation of diabetic patients getting services according to standards; from 6 indicators of the achievement of the nutrition program, only 4 indicators have reached the target, namely the percentage of toddlers weighed, the number of people/families who received education on growth and development monitoring, the percentage of pregnant women who received at least 90 tablets during pregnancy, and the percentage of pregnant women who were monitored for the consumption of 90 tablets during pregnancy; and from 2 indicators of the achievement of the immunization program, none has been achieved.